Selectivity and stability of zeolites [Ca]A and [Ag]A towards ethylene adsorption and desorption from complex gas mixtures - van Zandvoort, Ilona; van Klink, Gerard P.M.; de Jong, Ed; van der Waal, Jan C. (Microporous and mesoporous materials, 2018)
Producer gas originating from the gasification of biomass has a complex composition, especially compared to its coal or gas based counterparts. Separation of these mixtures is a crucial step in a commercial process, which can effectively be achieved by selective adsorption. In this paper the adsorptive separation of ethylene from a typical complex gas mixture containing N2, H2, CH4, C2H4, C2H6, CO and CO2 on zeolites [Ca]A and [Ag]A using a set-up for high throughput screening is described. It was shown that [Ca]A has a high ethylene adsorption capacity, whereas ethane and CO2 are co-adsorbed. Desorption of ethylene from [Ca]A is slow, but the adsorption capacity could be restored fully. In addition, the material is stable over 15 subsequent adsorption/desorption cycles without loss in performance. On the other hand, [Ag]A has a high adsorption selectivity for ethylene. However, its stability and ethylene recovery from the material is low, since only 80% of the original ethylene adsorption capacity was recovered after the first cycle. The adsorption capacity and selectivity decreases even further in subsequent cycles. This decrease in adsorption capacity and selectivity is caused by the reduction of the Ag+ ion to metallic silver and agglomeration to larger particles due to the presence of reducing gases, e.g. ethylene, CO and H2, in the gas stream. [Display omitted] •[Ca]A adsorbs ethylene, ethane and CO2 from a mock up gasifciction gas stream also containing methane, CO and H2.•Fresh [Ag]A selectively adsorbs ethylene from the mock up gasifciction gas stream.•[Ag]A looses ethylene selectivity and capacity over 15 repeated adsorption-desorption cycles.